Highly sensitive frequency selective surface for structural health monitoring system - S. A. Suhaimi; S. N. Azemi; P. J. Soh; C.B.M. Rashidi; A Abdullah Al-Hadi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper is introduced a passive sensor to detect the performance of the structure using three-dimensional (3D) Frequency Selective Surfaces (FSS). The proposed 3D Circular FSS results are proved behave as passive sensor with changing of sensitivity incident angles to be apply in Structural Health Monitoring (SHM) system. Moreover, this 3D Circular FSS capable to operate without stand to any (DC/AC) power and very low cost in term of installation and maintenance.